Unsettling Notions of Planning Competence: Lessons from Studio-Based Learning with Indigenous Peoples. (March 2023) - Barry, Janice; Allan, Evan; Chandran, Deepa; Cook, James; Curtis, Brittany; Kostyniuk, Ashley; Mikulec, Philip; Searle, Meleana; Yau, Derek
Drawing on the instructor and student experiences of a service-based learning course with Indigenous peoples, this paper considers how studios develop the skills and competencies outlined by accrediting bodies. Yet, this approach to teaching and learning can also unsettle students' sense of professional competence and faith in the usefulness of conventional planning methods. In this case, unsettlement was a valuable and productive outcome that supported the development of a more critically reflective approach to working with Indigenous peoples and a newfound appreciation of the need to engage in disquieting conversations about the colonial underpinnings of the planning profession.